ANALYSIS OF MACROECONOMIC FLUCTUATIONS IMPACT ON EFFICIENCY AND ISLAMIC BANKING QUALITY 2015-2019 - Yudha, Ana Toni Roby Candra; Indrawan, Imam Wahyudi; Syarifudin, Syarifudin (Universitas Airlangga, 2021)
This study aims to analyze the impact of macroeconomic shocks, such as economic growth, inflation and the rupiah exchange rate on Islamic banking efficiency. This study uses the two-stage least squares (TSLS) method, which is a method with two endogenous variables, namely the non-performing financing (NPF) ratio as a representation of the quality of Islamic banking financing and the operating expense operating income (BOPO) ratio as a representation of Islamic banking efficiency. So that the TSLS method aims to purify these endogenous variables against stochastic disturbances. This study uses monthly data from January 2010 to January 2020, or as many as 121 observations. The observation of data is obtained from Islamic Banking Statistic that published by Financial Services Authority (OJK). The efficiency of Islamic banks is influenced by the number of sharia banking office networks, capital adequacy ratios, and NPF ratios. The NPF ratio itself is affected by macroeconomic conditions (economic growth and appreciation of the rupiah exchange rate) as well as the efficiency of Islamic banking. Based on the above findings, a number of recommendations were given, including the urgency of simultaneously increasing efficiency and quality of Islamic banking financing accompanied by monitoring Indonesia's macroeconomic conditions, so that it is hoped that Islamic banks will be more resilient to macroeconomic shocks and competitive in the national financial services industry.